Balancing Dignity, Equality and Religious Freedom: A Transnational Topic. (31st August 2017) - Pin, Andrea
Abstract : The concept of dignity has made its way into contemporary discourse on rights after having taken a winding road which intersected secular thinking with religious thinking. Its pervasive utilisation by courts shows its richness as well as its amorphousness. An enquiry into comparative law suggests that the concept of dignity, especially when it is associated with the idea of equality, creates tensions with claims to religious freedom. Such clashes cannot be reconciled on theoretical grounds, but only on practical ones, depending on context and according to proportionality scrutiny.